2004
DOI: 10.1017/s1431927604883326
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Chromium in Root Tissues of Eichhornia Crassipes (Mart.) Solms. in Cachoeira River - Brazil

Abstract: In the last years metal pollution has become one of the most important environmental problems. Concerning the high toxicity of these elements, both sensitive analytical measurements and methods for the control of the ecosystem are required to reveal and localize metals on organism. Due to high transportations rates and exchange phenomena of sediment bound metals and changes of imission concentrations, the estimation of pollution in aquatic systems like the river Cachoeira is problematic. Recent studies have de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The problem of Cr-bioaccumulation can be very important in the case of industrialexploited algae species, namely Gelidium genus species because of their ability to bioccumulate chromium, especially as Cr (III) salts (Vilar et al, 2007). Accumulation of chromium was also determined in some aquatic and floating plants, such as Eichhornia crassipes (Mangabeira et al, 2004), Hydrocotyle umbellata (Yongpisanphop et al, 2005), or Bacopa monnieri (Shukla et al, 2007), that can be used for wastewater treatment. An important question is about the usage of wetland plants such as Typha sp., Phragmites sp., Scirpus sp.…”
Section: Chromiummentioning
confidence: 99%
See 3 more Smart Citations
“…The problem of Cr-bioaccumulation can be very important in the case of industrialexploited algae species, namely Gelidium genus species because of their ability to bioccumulate chromium, especially as Cr (III) salts (Vilar et al, 2007). Accumulation of chromium was also determined in some aquatic and floating plants, such as Eichhornia crassipes (Mangabeira et al, 2004), Hydrocotyle umbellata (Yongpisanphop et al, 2005), or Bacopa monnieri (Shukla et al, 2007), that can be used for wastewater treatment. An important question is about the usage of wetland plants such as Typha sp., Phragmites sp., Scirpus sp.…”
Section: Chromiummentioning
confidence: 99%
“…Some workers reported that Cr (III) ions are highly stabilized by complex formation with organic molecules, such as proteins (glutathione), carbohydrates (especially pentoses), NAD(P)H, FADH 2 , and probably also with organic acids, and stored in root cell vacuoles in precipitated form or in apoplast in cell walls, which is the reason for restricted mobility of chromium in plants (Mangabeira et al, 2004). Transport of chromium is probably restricted only to vascular tissues.…”
Section: Chromiummentioning
confidence: 99%
See 2 more Smart Citations
“…When water quality is estimated in terms of the heavy metal concentrations, it is important that the sampling strategy includes characterizing the spatial variation in the pollutant concentration (Hedger, Atkinson, & Malthus, ; Mwamburi, ; Ouma & Mwamburi, ). Heavy metals can accumulate in high concentrations in animals and vegetable tissues (Marchand et al., ; Olivero‐Verbel et al., ; Palaniappan & Karthikeyan, ) and enter the food chain in multiple ways that can produce progressive toxic impacts attributable to its accumulation in different organs over the life cycle of an organism and long‐term exposure to a contaminated environment (Mangabeira et al., ).…”
Section: Introductionmentioning
confidence: 99%